Radial loaded transformed radial stub for LPF stopband extension - Ma, Kaixue (2013)
A low pass filter with ultra-wide band rejection and compact size using a proposed radial loaded transformed radial stubs is introduced and investigated. The implemented unite cell low pass filter with 1-dB cutoff frequency fc of 3.2 GHz demonstrates stopband rejection up to 11.8 fc i.e. 38 GHz. The design is further extended to the high-order LPF through cell cascading. The implemented four-cell LPF with fc of 3.6 GHz demonstrated 35dB rejection from 4.8GHz to 39GHz, 50 dB rejection from 5.4 GHz to 26 GHz (7.2 fc) and 20dB rejection from 4.4 GHz to 50 GHz (13.8 fc). The measured passband insertion loss is less than 1.7 dB, and group delay is from 0.45~0.8 nS. The size of the four-cell low pass filter is only 0.33λg × 0.135λg, (λg is the guide wavelength at center cutoff frequency) without using any lumped elements.